Czy warto dbać o reputację?: Eksperymentalne badanie wpływu informacji o jakości na funkcjonowanie rynków - Kuśmierczyk, Paweł (Does it Pay Have a Good Reputation? : Experimental Analysis of the Influence of Quality Information on the Functioning of Markets, 2005)
In the case of markets in which product quality pays important role for the customers, the situation of asymmetric information can often be observed. If the customer has difficulties with verifying the product quality and the credibility of producers’ declarations at the time of the purchase the producers might have to invent different strategies of quality signaling. The article describes the results of the experiments in which some participants played roles of producers who could produce the good of either “high” or “low” quality and who declared at the beginning of each session the quality of the good produced (the declaration didn’t have to be true). The rest of the participants playing the roles of the consumers were buying the good. The consumers could check the quality only through the costly tests or by observing the not market shares of each of the producers. Nevertheless this information could not serve as the quality guarantee as producers could set the level of their quality differently at the beginning of each session. Two games were played, first with 3 producers, 7 consumers and 8 sessions and second with 3 producers, 6 consumers and 6 sessions. At each of the games producers stared with high quality declarations, which were mostly honest at the beginning and deceptive as the final sessions were nearing. Generally two strategies of the producers could be observed: some of them tried to establish good reputation through high quality standards accompanied by high prices, whereas others were beginning to cheat quite soon and were trying to attract customers by lowering prices. Evan though the number of sessions was limited the high quality strategy turned out to be the most effective in both cases. As a conclusion it is noticed that even in the case of strong asymmetry of information the instruments such as the public information on market shares can play a significant role as the high quality signal. Gaining additional profits due to quality lowering turned out ineffective in the long run. Also the role of prices as the quality indicator should be of interest. Of course the conducted experiments were too limited to allow forming more decisive conclusions
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 23-41